(3GdbGfhf GdeajO aj YdGL GdMUi Hbhd SOjOs - (3YHO GdZfj Hf CHj SQMGf eSYhO GdRehQjs
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdYdGe (B: (3Ndb GdEfSGf ef fWaI CeTGL aLGA ai CMSf Jbhje hCHOY EMcGe s
(3BNQgG (B:s
(3gPG GfJgi Gdbhd ai GdHGH GdNGeS YTQ ai TQM eG hbY ef GdCOhjI GdeaQOI ai gPG GdcJGH hUdi Gddg Ydi fHjfG hehdGfG eMeO hYdi Bdg hUMHg hSde JSdjeG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B18 - (3U(B138s
(3Cdag GdCMeOi GdefUhQi GdSYOis
(3hPcQ ai ebOeJg Cfg GHJOC OQGSI GdWH hgh UZjQ GdSf SfI (B994 (3Ydi jO CHj eMeO bGSe Hf eMeO GdZSGfi GdedbH HGdhRjQs
(3hQJHI Ydi NeSI YTQ HGHkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH (B- (3U (B179 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs